Thinking and Prospect of Power Chip Specificity - Fuqi Ma; Min Li; Xuzhu DONG; Bo WANG; Yinyu ZHOU; Jincan Li; Lei FENG; Mohamed A. Mohamed (International Journal of Photoenergy)
The contradiction between the demand of massive intelligent scene caused by the interconnection of things in power system and the bottleneck of the chip itself is becoming more and more serious. How to realize the self-controllable and domestic substitution of power chips has been widely concerned in the power field. Therefore, this paper analyzes the demand for power chips in power system and discusses the scene specificity of power chips. Then, it combs the design architecture of power chips and discusses the application scenarios and research focuses of power chips. Finally, the key scientific problems and major technical bottlenecks of power chips are prospected.